Hospital Librarians' Contributions to Health Services' Accreditation: An Account of the Health Libraries for the National Safety and Quality in Health Services Standards (HeLiNS) Research Project, 2016-18. Issue 2 (2nd April 2020) - Ritchie, Ann; Gilbert, Cecily; Gaca, Michele; Siemensma, Gemma; Taylor, Jeremy
ABSTRACT: This article documents the Health Libraries for the National Standards (HeLiNS) research project. The project received the ALIA 2016 research award and was undertaken by a collaboration of the ALIA/Health Libraries Australia and Health Libraries Inc groups. The research aimed to explore the contributions made by Australian hospital libraries to assist their organisations to achieve accreditation against the National Safety and Quality for Health Services (NSQHS) Standards. The research clearly demonstrates that hospital libraries are integral to a hospital's quality and safety systems. They make substantial and essential contributions through their professional information/knowledge management services and by ensuring access to evidence-based resources. The research found that there are varying levels of contributions, however, and it is suggested that these differences may be influenced by variables such as location and size of hospital. It is further suggested that for hospitals without a library service, or those with libraries that have limited capacity to deliver professional services and resources, there is likely to be an 'evidence-accessibility gap', and they may be at risk and not performing as well as they could in regard to NSQHS accreditation standards, and safety and quality systems.